MILK PRODUCTION AND REPRODUCTIVE TRAIT CAUSED BY LOC514211 GENE MUTATION IN DAIRY COWS - A. S. Anggraeni; E. Kurnianto; S. Johari; S. Sutopo; Z. Shujun (Journal of the Indonesian Tropical Animal Agriculture, 2015)
The SNP (rs 42688595) in LOC514211 isuncharacterized gene and located in chromosome 13 in Bos taurus,hadsignificant effectson milk yieldand milk qualitythat have been identified from Chinese and British dairy cowsusing GWAS (Genome-wide Association Study) based on 60k SNP-Chipin the previous study. The objective of this study wasto confirmthe effects ofthe SNP in LOC514211onproductive traitsin another population of Chinese Holsteindairy cow. Four hundred and seventy dairy cows were use in this study,genomicDNA was extracted from the blood of dairy cow, PCR-RFLP wasapplied to genotype of these DNA samples. Analysis of Variance (ANOVA) was performed by the General Linear Model (GLM) procedure of SAS 9.13 to identifythe association of SNP with milk and reproductivetraits. Results showed that SNP inLOC514211was polymorphic in this herd of dairy cowand wasin Hardy-Weinberg disequilibrium,and had significant differencesamong genotype in milk yield, milk quality and reproductive traits, whichwere similar with the results of previous GWAS study based SNP-Chips. Inconclusion, indicated that thisSNP in LOC514211 might bepotential markersforboth milk and reproductivetraits.